Cluster randomised controlled trial of an online intervention to improve healthy food purchases from primary school canteens: a study protocol of the ‘click & crunch’ trial - Karen Campbell; Rachel Sutherland; Luke Wolfenden; Nicole Nathan; Sze Lin Yoong; Chris Rissel; Penny Reeves; Rebecca Wyse; Tessa Delaney; Pennie Gibbins; Kylie Ball; Kirsty Seward; et al. (BMJ Open)
Introduction School canteens are the most frequently accessed take-away food outlet by Australian children. The rapid development of online lunch ordering systems for school canteens presents new opportunities to deliver novel public health nutrition interventions to school-aged children. This study aims to assess the effectiveness and cost-effectiveness of a behavioural intervention in reducing the energy, saturated fat, sugar and sodium content of online canteen lunch orders for primary school children.Methods and analysis The study will employ a cluster randomised controlled trial design. Twenty-six primary schools in New South Wales, Australia, that have an existing online canteen ordering system will be randomised to receive either a multi-strategy behavioural intervention or a control (the standard online canteen ordering system). The intervention will be integrated into the existing online canteen system and will seek to encourage the purchase of healthier food and drinks for school lunch orders (ie, items lower in energy, saturated fat, sugar and sodium). The behavioural intervention will use evidence-based choice architecture strategies to redesign the online menu and ordering system including: menu labelling, placement, prompting and provision of feedback and incentives. The primary trial outcomes will be the mean energy (kilojoules), saturated fat (grams), sugar (grams) and sodium (milligrams) content of lunch orders placed via the online system, and will be assessed 12 months after baseline data collection.Ethics and dissemination The study was approved by the ethics committees of the University of Newcastle (H-2017–0402) and the New South Wales Department of Education and Communities (SERAP 2018065), and the Catholic Education Office Dioceses of Sydney, Parramatta, Lismore, Maitland-Newcastle, Bathurst, Canberra-Goulburn, Wollongong, Wagga Wagga and Wilcannia-Forbes. Study results will be disseminated through peer-reviewed publications, reports, presentations at relevant national and international conferences and via briefings to key stakeholders. Results will be used to inform future implementation of public health nutrition interventions through school canteens, and may be transferable to other food settings or online systems for ordering food.Trial registration number ACTRN12618000855224.